Criteria for Patients using Crystalloid and Colloid Fluids in Sectio Caesaria - Emanuel Ileatan Lewar; Dwi Arymbhi Sanjaya; I Gede Agus Shuarsedana Putra (JURNAL KESEHATAN PRIMER, 2018)
Background: In Indonesia, the study about effectivity and side effect of colloid and crystalloid fluid have been completed, but the sample on the study was varied. The aim of this research was to describe the criteria of patient which used of crystalloid and colloid fluids on blood pressure in sectio caesarea by using spinal anesthesia techniques. Method: The research employed a descriptive quantitative method by using a questionnaire. The basic features of crystalloid and colloid fluid selection were analyzed by multiple response tests. This research was conducted in type A hospitals in the Denpasar area by involving 30 anesthesiologist as a respondent. Result: The results indicated that 100% of respondents stated that they used crystalloid for patient with allergic and they used coloid for patient with high risk edema. The result has been reviewed with The National Guideline of Medical Services for Anesthesiology and Incentive Therapy have been followed in determining the use of crystalloid and colloid fluids at section Caesarea. However, the guideline did not explain the basis for selecting crystalloid and colloid fluids to prevent maternal hypotension in sectio caesarea by using spinal anesthesia techniques, therefore the factors of effectiveness and risk of side effects are the main consideration.